Зварювальні апарати для Li-ion акумуляторів - Бойко, К. С. (ХНУРЕ, 2025)
The work describes the types of welding machines for Li-ion batteries, gives the results of studies of the influence of current and pulse duration on the quality of welding tapes of different materials and thicknesses.
Keywords: Li-ion акумулятор; зварювальний апарат